Social and Religious Approaches in Marriage Counseling Due to Adultery: Strategies for Building Legal and Moral Awareness in the Al-Barakah Islamic Study Group - Ridwan Bani Shaleh; Syarifatul Ulfa; Siti Kulsum; Oyoh Bariah (al-Afkar, Journal For Islamic Studies, 2025)
Promiscuity among young people often has negative impacts, such as early marriage or pregnancy out of wedlock. Pregnancy before marriage is a serious issue that confuses many parties, including parents, teachers and community leaders. In situations like this, parents often feel embarrassed and try to find solutions to save the family's good name. Marriage itself is an inner and outer bond between a man and a woman, with the aim of forming a harmonious and eternal family based on divine values. According to some scholars, the legal origin of marriage is mubah (permissible) if it is related to al-ahkam al-khamsah. However, in practice, marriage is often seen as a way to fulfill one's physical or biological needs. This phenomenon occurs more and more often in modern life. Pregnancy out of wedlock is a consequence of sexual relations before marriage. In Indonesia, women who become pregnant out of wedlock are usually married off immediately. Such marriages, known as "pregnancy marriages," may be with the man responsible for the pregnancy or with another man. This article will discuss social and religious approaches in providing counseling about marriage due to adultery, with a focus on strategies to increase legal and moral awareness in the Al-Barakah Ta'lim Council.